Refleksi Berbasis Video dalam Pembentukan Kesadaran TPACK Mahasiswa PGSD pada Micro Teaching IPAS SD: Studi Kasus di Program Studi PGSD - Subhanadri Subhanadri; Opi Andriani; Nurlev Avana; Missi Febriani (CV. Master Literasi Indonesia, 2026)
This study aims to explore the process of forming TPACK (Technological Pedagogical Content Knowledge) awareness in PGSD (Elementary School Teacher Education) students through video-based reflection in Micro Teaching IPAS SD courses. This research uses a qualitative approach with an instrumental case study design. The research subjects were six PGSD students who were taking the Micro Teaching course in the 2025/2026 academic year, focusing on IPAS SD Merdeka Curriculum material for grades IV-VI. Video-based reflection was carried out in three teaching simulation cycles, each consisting of stages: micro lesson plan preparation, teaching simulation, independent video viewing, structured group reflection sessions, and reflective interviews. Data was collected through structured observation, semi-structured interviews, RPP document analysis, and recorded video-based reflection sessions. Data analysis used the Miles, Huberman, and Saldana (2014) model through data condensation, data presentation, and conclusion drawing, with data validity ensured through source triangulation, member checking, and audit trail. The results show that video-based reflection effectively encourages the formation of TPACK awareness through a cyclical process of planning, practice, self-observation, and reflective discussion. The TPK and PCK aspects showed the most significant development, while the TCK aspect required more scaffolding. Supporting factors include conducive group reflection dynamics and structured reflection protocols, while inhibiting factors include students' initial discomfort when watching their own recordings and limited variety of digital technology mastery.